Fission yeast Stn1 is crucial for semi-conservative replication at telomeres and subtelomeres - Takikawa, Masahiro; Tarumoto, Yusuke; Ishikawa, Fuyuki (Nucleic acids research, 2017)
The CST complex is a phylogenetically conserved protein complex consisting of CTC1/Cdc13, Stn1 and Ten1 that protects telomeres on linear chromosomes. Deletion of the fission yeast homologs stn1 and ten1 results in complete telomere loss; however, the precise function of Stn1 is still largely unknown. Here, we have isolated a high-temperature sensitive stn1 allele (termed stn1-1). stn1-1 cells abruptly lost telomeric sequence almost completely at the restrictive temperature. The loss of chromosomal DNA happened without gradual telomere shortening, and extended to 30 kb from the ends of chromosomes. We found transient and modest single-stranded G-strand exposure, but did not find any evidence of checkpoint activation in stn1-1 at the restrictive temperature. When we probed neutral-neutral 2D gels for subtelomere regions, we found no Y-arc-shaped replication intermediates in cycling cells. We conclude that the loss of telomere and subtelomere DNAs in stn1-1 cells at the restrictive temperature is caused by very frequent replication fork collapses specifically in subtelomere regions. Furthermore, we identified two independent suppressor mutants of the high-temperature sensitivity of stn1-1: a multi-copy form of pmt3 and a deletion of rif1. Collectively, we propose that fission yeast Stn1 primarily safeguards the semi-conservative DNA replication at telomeres and subtelomeres.